Identification Obstacles Biology Learning using Sharing and Jumping Task on Didactical Design Research - Zuni Mitasari; Yuswa Istikomayanti; Anis Samrotul Lathifah (Indonesian Journal of Biology Education, 2023)
The purpose of this study is identify student learning barriers in other classes. This type of research is descriptive qualitative. This research method is Didactical Design Research (DDR), which consists of three stages, namely (1) prospective analysis, (2) metapedadidactical analysis, and (3) retrospective analysis. The results of this study are (1) Student learning obstacle are included in epistemological barriers, namely student knowledge with limited application contexts. Students have not been able to understand the concept thoroughly and have not been able to connect one concept to another and (2) Analysis of learning barriers aims to be used as a reference in the preparation of learning tools and to predict didactic responses and anticipations that occur during the learning process.